Subtypes of Premorbid Metabolic Syndrome and Associated Clinical Outcomes in Older Adults - Lin, Chu-Sheng; Lee, Wei-Ju; Lin, Shih-Yi; Lin, Hui-Ping; Chen, Ran-Chou; Lin, Chi-Hung; Chen, Liang-Kung (Frontiers in Medicine, 2022)
Introduction Metabolic syndrome has been shown to be a risk for new onset of cardiovascular disease and type 2 diabetes. The subclasses of metabolic syndrome and associated adverse health outcomes remain obscure. The study aimed to explore potential subtypes of metabolic syndromes and their associations with incidental diabetes, and major adverse cardiovascular events (MACE). Methods Data of the retrospective cohort study exercperted from the New Taipei City Elderly Health Examination Database in 2014 and 2016. Demographic data and status of metabolic syndrome as well as its components and latent class analysis were analyzed. All participants were aged 65 years and older, and those with prior history of cardiovascular disease, cerebrovascular disease, diabetes mellitus and current use of medications for hypertension, diabetes, and dyslipidemia were excluded. Results Total of 4,537 senior citizens participating were enrolled, and 2,207 (48.6%) of them were male. The prevalence of metabolic syndrome and central obesity increased with age. A 4-latent class model was fitted for participants with metabolic syndrome. The ABD+GLU+HDL+BP group had the highest HR for predicting new onset of diabetes. The ABD+ HDL+BP group had a high risk of cardiovascular disease and MACE compared after 2 years of follow-up. Conclusions This epidemiological analysis demonstrated that risks of developing new onset diabetes, cardiovascular disease, and MACE varied among the different subtypes of metabolic syndrome.